Tourism Marketing: Banyuwangi Regency Government Partnership with Local Mass Media in Banyuwangi: Pemasaran Pariwisata: Kemitraan Pemerintah Kabupaten Banyuwangi dengan Media Massa Lokal di Banyuwangi - Niko Pahlevi Hentika; Erna Agustina (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Banyuwangi Regency is one of the districts that is currently aggressively developing tourism potential. This development has been carried out since Regent Abdullah Azwar Anas. This is because the natural and cultural potential that Banyuwangi has is very good for tourism. One way to develop this is through partnerships in various fields. One of the most important areas in tourism development is partnerships in the field of tourism marketing. The partnership carried out so far is between the Banyuwangi Regency government and local mass media. Because of the above phenomenon, this qualitative-descriptive research is deemed necessary. The main aim of this research is to describe, analyze and interpret the partnership between the Banyuwangi Regency Government and local mass media in tourism marketing governance in Banyuwangi. Data collection methods were carried out by interviews, documentation and observation. The research results show that the two partnering parties, namely the Banyuwangi Regency Government and the local mass media play a mutual role. In addition, the model partnership between governments Banyuwangi and local mass madia is mutualism partnership